Assessment of primary stability of immediate implants placed in the maxillary and mandibular anterior region using resonance frequency analysis - M Viswambaran; Kamal Verma (Wolters Kluwer Medknow Publications, 2020)
Background: A matter of controversy in implant dentistry concerns the most appropriate method to determine implant stability. Many methods have been reported in the literature including periotest and resonance frequency analysis (RFA). However, there is no consensus regarding the ideal method to determine implant stability. Materials and Methods: A total of 50 patients male and female in the age group of 18-38 years, each having at least one tooth indicated for extraction (either maxillary or mandibular anterior teeth) were selected. Fifty Xive implants (Friadent, Dentsply, Germany) were placed into fresh extraction sockets and immediately loaded. Implants were evaluated by clinical and radiographic methods. Implant stability was measured using periotest and RFA at the time of implant placement, 3 months, 6 months, 9 months, and 12 months postoperatively. Results: The mean mobility values for periotest decreased over a period of observation, and all implants consistently produced readings between −8 and + 7. The RFA values during the period of observation increased, and it was in the range of 49-100. Statistical analysis using regression analysis showed that percentage improvements in stability during each period were statistically highly significant in respect of periotest and RFA (P = 0.0001). Conclusions: A clinical trend of an implant stability quotient (ISQ) of more than 49 with a range of 49-98, is probably descriptive of osseointegrated implants. However, according to our experience, implants with a primary stability above 50 ISQ may be sufficient for successful immediate loading while implants below 40 could be dealt with caution and conventional loading can be considered in such cases.